Suggestions for the extension of the jurisdiction of the Civil Bill and Quarter Sessions Courts in Ireland - Malley, George Orme (Statistical and Social Inquiry Society of Ireland, 1872)
In bringing this important question again under the notice of the members of this Society, and through them of the public, I should consider it necessary to apologise for its re-introduction, were it not that every class in the community, especially in the rural districts, look forward to the long promised legislation on the subject with expectations which cannot be much longer delayed or disregarded. The nature of the question and the extent to which the amendments I am about to recommend have already been sanctioned in England, and the precedents which exist for carrying them into practice, renders it unnecessary and unadvisable for me to adopt the plan lately recommended by influential members of this Society, of drafting a bill on the subject. Such a task would be more fatiguing on the hand than on the head, as it would, to a great extent, consist of transcribing existing statutes, with such modifications as would be suited to this country and the circumstances of the people, and a few important innovations, the details of which are capable of being easily supplied.
Read before the Society, 20 February 1872
Keywords: Legal system in nineteenth century Ireland; Civil Bill courts in Ireland; Quarter Sessions courts in Ireland; 314.15